Construction of several plant expression vectors using multiple cell wall degrading enzyme genes from Trichoderma harzianum and rice transformation - LIU Mei; SUN Zong-xiu; XU Tong (浙江大学学报. 农业与生命科学版, 2004)
In order to enhance rice resistance against fungal pathogens by applying the synergistic interaction of different cell wall degrading enzymes from Trichoderma, three different cell wall degrading enzyme genes from Trichoderma harzianum PI were placed respectively downstream of Act1 promoter. Based on this work, 7 different plant expression vectors were constructed by cloning each gene alone or either two genes in combination or three genes together into binary vector pCAMBIA1305.2. Three kinds of methods was used to solve different problems in the process of vector construction: (1) Restriction solution was used directly to ligation reaction for recovered DNA fragment usually influenced ligation frequency; (2) Using one cohensive end and one blunted end to carry out the ligation reaction was more effective than two blunted ends when restriction ends must be modified; (3) Choosing appro-priate mediated plasmid to introduce new restriction sites around certain DNA fragment and avoid linear ends modification. The constructed vectors also carried hpt gene and Gus gene which was already placed in two sides of the multiple cloning sites of binary vector pCAMBIA1305.2, that provided a suit of systematic materials for further study on the influence of T-DNA size, gene combination and gene direction on transformation frequency and gene expression. Seven combinations of CWDE genes were transformed into Oryza sativa L ssp. Japonic a cv. Ishikari-shiroge respectively mediated by Agrobacterium tumefaciens. More than 1, 800 independent regenerated plantlets of seven populations were obtained. PCR analysis of part of transgenic plants revealed that about 96 percent of them integrated with at least one out of three exogenous genes, more than 80 percent had intact exogenous fragment.